Análise da relação entre doações eleitorais e as contratações de obras públicas e serviços de engenharia no Estado do Ceará - Filgueiras, Emiliana Leite (2019)
This study tests the impact of electoral donations on a possible beneficiation of donor companies in terms of contracting public works and engineering services carried out by the Government of the State of Ceará. For this purpose, the Differences in Differences estimator was used, with a sample record to control the self-selection bias, and the Differences in Differences with Pairing by Propensity Score, in order to control the observable characteristics. Data were collected from 1,218 contracts for works and engineering services with values above R$ 1.5 million, celebrated in the period from 2008 to 2018 with 278 companies. The results of the estimations did not allow to affirm that the companies that made donations to elected candidates were benefited in terms of contractual volume. It was observed that companies concentrate their donations on candidates connected to the current government and that the interactions between donors and politicians are not restricted to a single electoral period.